Time-encoding VCO-ADCs for Integrated Systems-on-Chip Principles, Architectures and Circuits - Gielen, Georges; Hernandez-Corporales, Luis.; Rombouts, Pieter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book demonstrates why highly-digital CMOS time-encoding analog-to-digital converters incorporating voltage-controlled oscillators (VCOs) and time-to-digital converters (TDCs) are a good alternative to traditional switched-capacitor S-D modulators for power-efficient sensor, biomedical and communications applications. The authors describe the theoretical foundations and design methodology of such time-based ADCs from the basics to the latest developments. While most analog designers might notice some resemblance to PLL design, the book clearly highlights the differences to standard PLL circuit design and illustrates the design methodology with practical circuit design examples. Describes in detail the design methodology for CMOS time-encoding analog-to-digital converters that can be integrated along with digital logic in a nanometer System on Chip; Assists analog designers with the necessary change in design paradigm, highlighting differences between designing time-based ADCs and traditional analog circuits like switched-capacitor converters and PLLs; Uses a highly-visual, tutorial approach to the topic, including many practical examples of techniques introduced.
Time-based and VCO-ADCs from a signal processing perspective -- Quantization noise, thermal noise, flicker noise, phase noise (PSS) and clock jitter in VCO-ADCs -- Overview of VCO-ADC architectures -- Oscillators: ring oscillators and their design methodology; other oscillators -- Design techniques-practical example -- Closed-loop VCO-ADC architectures -- Practical design cases.
Keywords: Electronic circuits; Telecommunication; Embedded computer systems; Electronic Circuits and Systems; Microwaves, RF Engineering and Optical Communications; Embedded Systems; Analog-to-digital converters; Voltage-controlled oscillators; Integrated circuits